Exacerbated Neuropathy in POLAR A and M Trials Due to Redox Interaction of PledOx-Associated Mn2+ and Oxaliplatin-Associated Pt2+ - Jan Olof G. Karlsson; Per Jynge; Louis J. Ignarro (MDPI AG, 2023)
Disappointing results from the POLAR A and M phase III trials involving colorectal cancer patients on chemotherapy with FOLFOX6 in curative (A) and palliative (M) settings have been reported by the principal investigators and the sponsor (PledPharma AB/Egetis Therapeutics AB). FOLFOX6, oxaliplatin in combination with 5-fluorouracil (5-FU), possesses superior tumoricidal activity in comparison to 5-FU alone, but suffers seriously from dose-limiting platinum-associated Chemotherapy-Induced Peripheral Neuropathy (CIPN). The aim of the POLAR trials was to demonstrate that PledOx [calmangafodipir; Ca4Mn(DPDP)5] reduced the incidence of persistent CIPN from 40% to 20%. However, this assumption was based on "explorative" data in the preceding PLIANT phase II trial, which did not mirror the expected incidence of unwanted toxicity in placebo patients. In POLAR A and M, the assessment of PledOx efficacy was conducted in patients that received at least six cycles of FOLFOX6, enabling analyses of efficacy in 239 A and 88 M patients. Instead of a hypothesized improvement from 40% to 20% incidence of persistent CIPN in the PledOx group, i.e., a 50% improvement, the real outcome was the opposite, i.e., an about 50% worsening in this bothersome toxicity. Mechanisms that may explain the disastrous outcome, with a statistically significant number of patients being seriously injured after having received PledOx, indicate interactions between two redox active metal cations, Pt2+ (oxaliplatin) and Mn2+ (PledOx). A far from surprising causal relationship that escaped prior detection by the study group and the sponsor. Most importantly, recently published data (ref 1) unequivocally indicate that the PLIANT study was not suited to base clinical phase III studies on. In conclusion, the POLAR and PLIANT trials show that PledOx and related manganese-containing compounds are unsuited for co-treatment with platinum-containing compounds. For use as a therapeutic adjunct in rescue treatment, like in ischemia-reperfusion of the heart or other organs, or in acetaminophen (paracetamol)-associated liver failure, there is little or nothing speaking against the use of PledOx or other PLED compounds. However, this must be thoroughly documented in more carefully designed clinical trials.